Penguatan Kompetensi Sumber Daya Manusia Satpam Melalui Pelatihan Disiplin, Tanggung Jawab, Dan Integritas Kerja Pada PT. Rafaradis Jaya Abadi Pekanbaru - Adriansyah, Henry Martin (EL-EMIR INSTITUTE, 2025)
This community service activity aims to enhance the understanding and transformational leadership competencies of leaders and employees in facing the challenges of the modern workplace at PT. Rafaradis Jaya Abadi Pekanbaru. The implementation method was carried out through the stages of preparation, implementation, and evaluation. The training was conducted using a participatory approach through lectures, discussions, case studies, and simulations focusing on the concepts and practical application of transformational leadership in the workplace. The results indicate an improvement in participants’ understanding of transformational leadership principles, a shift in attitudes toward more collaborative leadership patterns, and increased readiness to apply inspirational, adaptive, and human resource development–oriented leadership styles. The training also had a positive impact on raising awareness of the importance of effective communication, work motivation, and innovation in the modern work environment. The recommendation from this activity is the need for continued training and ongoing mentoring to ensure the optimal implementation of transformational leadership and to support sustainable organizational performance improvement